ANALISIS KEMAMPUAN BERFIKIR KRITIS MATEMATIS SISWA SMA IMMANUEL SINTANG - Jiran Dores, Olenggius; Surendra, Rosalia Vera; Merayang, Martinus Viensius (Department of Mathematics Education , University of Jember, 2022)
Abstrack This study aims to determine the ability to think critically mathematically based on the learning motivation of high school students. The method in this study uses a descriptive qualitative approach. The population in this study was in one of the Immanues Sintang High Schools and the number of samples was 17 students with heterogeneous abilities. The instrument in this study was a test of critical thinking skills with a total of five test items and a non-test in the form of a questionnaire to determine the characteristics of students consisting of 32 question scales. The results of this study showed that the ability to think critically mathematically based on the results of the test questions showed that the ability to think was lacking, almost 59 % of students got scores below completeness but seen from high learning motivation so that 41 % of students showed a positive attitude and were enthusiastic in working on the questions.